Risk and Outcome after Simultaneous Carotid Surgery and Cardiac Surgery: Single Centre Experience - Theodor Tirilomis; Dieter Zenker; Tomislav Stojanovic; Stella Malliarou; Friedrich A. Schoendube (International Journal of Vascular Medicine)
Objective. Carotid artery stenosis in patients undergoing open-heart surgery may increase risk and deteriorate outcome. The aim of the study was the analysis of risks and outcome after simultaneous carotid and cardiac surgery. Methods. We retrospectively reviewed the medical records of 100 consecutive patients who underwent simultaneous carotid surgery and open-heart surgery during a 5-year period (from 2006 to 2010). Seventy patients were male and 30 female; the mean age was 70.9±7.9 years (median: 71.8 years). Seventy-three patients underwent coronary bypass grafting (CABG), 18 patients combined CABG and valve procedures, 7 patients CABG combined with other procedures, and 3 patients isolated valve surgery. More than half of patients had had bilateral carotid artery pathology (n=51) including contralateral carotid artery occlusion in 12 cases. Results. Carotid artery patch plasty was performed in 71 patients and eversion technique in 29. In 75 cases an intraluminal shunt was used. Thirty-day mortality rate was 7% due to cardiac complications (n=5), metabolic disturbance (n=1), and diffuse cerebral embolism (n=1). There were no carotid surgery-related deaths. Postoperatively, transient cerebral ischemia occurred in one patient and stroke with mild permanent neurological deficit (Rankin level 2) in another patient. Conclusion. Simultaneous carotid artery surgery and open-heart surgery have low risk. The underlying cardiac disease influences outcome.